Large Scale 3D Printing: Influence of Fillers on Warp Deformation and on Mechanical Properties of Printed Polypropylene Components. Issue 1 (17th November 2021) - Winter, Kevin; Wilfert, Jonas; Häupler, Bernhard; Erlmann, Jonas; Altstädt, Volker
Abstract: Additive manufacturing processes are still on the way from a prototyping process to an established serial production process. Often the limiting factors are the variety and costs of materials compared with standard materials. Polypropylene is a commonly used material in series production. The processing of polypropylene in additive‐ and extrusion‐based manufacturing processes is still a challenge. A big issue in pellet‐based large scale additive manufacturing of polypropylene is to achieve dimensional accuracy of the printed parts. Due to the semi‐crystalline nature of polypropylene and its low adhesive force on standard printing surfaces (aluminum) the fabricated parts tend to warp and deviate from the geometric shape. In this paper the influence of a melt adhesive and different filler types (glass fibers, glass bubbles, and talcum) on the warpage behavior of 3D printed polypropylene parts is investigated. Another issue in additive manufacturing is the mechanical properties of the fabricated parts compared to injection molded parts. The mechanical properties of 3D printed parts often show a dependency on the print direction, especially in case of using fillers with an anisotropic shape (fibers). In this study the influence of different fillers on mechanical properties and process indicated orientation is analyzed. Abstract : A big issue in pellet‐based additive manufacturing of polypropylene is to achieve dimensional accuracy of the printed parts. Due to its semi‐crystalline nature and low adhesive force on standard printing surfaces the fabricated parts tend to warp. In this approach the influence of a melt adhesive and different filler types on the dimensional accuracy and the mechanical properties are investigated.